Ecological security evaluation and ecological regulation approach of East-Liao River basin based on ecological function area - Mingxi Zhang (Elsevier, 2021)
Watershed ecological security provides the basic guarantee of regional sustainable development; thus, reliable watershed ecological security evaluation is of great significance in revealing the watershed ecological security status and promoting the healthy development of the watershed society and ecological environment. To construct the ecological function area, this study used the East-Liao River basin as the analysis object and discussed the delimitation method of ecological security evaluation, which provided the reference and basis for studying and exploring the optimal ecological regulation method of the basin. The following results were obtained: from 2000 to 2020, the regions with lower ecological security index changed from northwest to southeast of the watershed, and presented the spatial distribution of “unsafe” → “generally safe” → “relatively safe” → “safe”, with the center of gravity concentrated in the middle of the watershed; the spatial differences of ecological security became significant with the addition of ecological function zones, and they show a certain spatial aggregation trend; from 2000 to 2020, the ecological security level was predominantly safer, and the distribution of gravity center showed a circular state; the ecological security level of the watershed can be improved by adjusting the proportion of regional land use types. According to the results, countermeasures and approaches of watershed ecological security regulation were suggested, and four subareas were established: forbidden development zones, traditional utilization zones, ecologically sensitive/fragile zones, and key ecological function zones; this would provide a basis for further analysis of environmental governance in the East-Liao River basin of Jilin Province. Nevertheless, the countermeasures and approaches of ecological security regulation proposed in this study will also be useful for land use planning and runoff management in other watersheds around the world.